1985
DOI: 10.1104/pp.78.3.510
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Cytokinin Biosynthetic Sites in Pea Plants and Carrot Roots

Abstract: ABSTRACE MATERIALS AND METHODSThe biosynthesis of cytokinins was examined in pea (Pisum sativum L.) plant organs and carrot (Daucus carota L.) root tissues. When pea roots, stems, and leaves were grown separately for three weeks on a culture medium containing 18-"4Cadenine without an exogenous supply of cytokinin and auxin, radioactive cytokinins were synthesized by each of these organs. Incubation of carrot root cambium and noncambium tissues for three days in a liquid culture medium containing 18-'Cladenine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(68 citation statements)
references
References 15 publications
5
62
0
1
Order By: Relevance
“…However, the observation that decapitation induces parthenocarpy in the absence of roots (the main purported source of cytokinins; Chen et al, 1985), as far as the mature leaves were present in the plant (Table I), does not support the idea of cytokinins being involved in stimulating fruit growth on decapitated plants. The possibility cannot be discarded that mature leaves and/or the stem, organs also capable of cytokinin biosynthesis (Chen et al, 1985), are a source of these hormones.…”
Section: Martínez Andmentioning
confidence: 60%
“…However, the observation that decapitation induces parthenocarpy in the absence of roots (the main purported source of cytokinins; Chen et al, 1985), as far as the mature leaves were present in the plant (Table I), does not support the idea of cytokinins being involved in stimulating fruit growth on decapitated plants. The possibility cannot be discarded that mature leaves and/or the stem, organs also capable of cytokinin biosynthesis (Chen et al, 1985), are a source of these hormones.…”
Section: Martínez Andmentioning
confidence: 60%
“…However, because direct regulation of the IPT gene by auxin, rather than crude decapitation, has not been demonstrated, a direct link between the two cannot be made. Chen et al (1985) have demonstrated biochemically that, in roots, cambial tissue is responsible for cytokinin synthesis, but the site of synthesis in stems has not been reported. Identification of this site by in situ localization of the putative IPT gene or biochemical assay, and correlation with the site of auxin action described here, provide further support for a role for auxin in the regulation of cytokinin biosynthesis.…”
Section: Relationship Between Auxin and Cytokinin In The Regulation Omentioning
confidence: 99%
“…It is thought that auxin acts to control the concentration of cytokinin derived from the roots (Bangerth, 1994). Cytokinins are produced not only in the root, however, but also in the shoot (Chen et al, 1985). Cytokinin concentrations in bean xylem exudate of bean after decapitation increase within 16 h and gradually return to basal levels (Bangerth, 1994), and those in chickpea axillary buds after decapitation increase 7-fold by 6 h and 25-fold by 24 h (Turnbull et al, 1997), suggesting that cytokinins are necessary to initiate outgrowth of axillary buds.…”
Section: Physiological Approachmentioning
confidence: 99%